Gender and informal sector analysis in India: Economy wide approaches - Anushree Sinha; Haider A. Khan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
The main purpose of this paper is to look at the incorporation of gender and the informal sector within a general equilibrium framework for India. Moreover, we clarify some important links between a gender aware informal sector based social accounting matrix (SAM) and general equilibrium models such as the computable general equilibrium (CGE) models including as a special case the fixed price multiplier (FPM) models. In particular, economy wide modelling of gender and the informal sector is facilitated by the use of national level data and constructing the base data set as an SAM. Another important strategy is to conceptualize the economy within gender structures, entailing the recognition of gender relations as an intervening variable in all economic activities.
Keywords: D58; O17; J16; 330; general equilibrium; informal sector; gender; Informeller Sektor; Geschlecht; Allgemeines Gleichgewicht; CGE-Modelling; Social Accounting Matrix; Indien